The experiences of high-performance coaches in the management of difficult athletes. (November 2020) - Heelis, William J.; Caron, Jeffrey G.; Bloom, Gordon A.
Abstract: Although research on effective coaching strategies is well documented, researchers are still learning how coaches effectively manage problematic athletes. The purpose of this study was to investigate how high-performance coaches managed difficult athletes. We interviewed eight experienced ice hockey coaches from the premiere development stream in Canada for athletes who aspire to play professionally. Through our analysis of the data, we found that these coaches identified problem athletes early, fostered relationships, provided clear expectations and roles, and transformed their behaviors to match the team culture (although this was not always possible). We also found that managing difficult athletes takes a great deal of patience, introspection, and emotional intelligence on the coach's behalf. Our findings contribute to a limited understanding of the knowledge and strategies used by coaches to manage difficult athletes and maintain a positive team climate. Highlights: We used a variety of methods to collect data in this qualitative study: individual interviews, relational mapping, and narrative timelines. The ice hockey coaches in this study said they managed difficult athletes by: identifying and addressing concerns early, clarifying expectations and roles, enforcing consequences, and transforming negative behaviors into positive ones. When difficult athletes were unable to transform their behaviors, the coaches said they had to deselect or trade these individuals in order to preserve the team culture. The effective management of difficult athletes is highly relational and involves social actors who are both internal (head coach, assistant coaches, athlete leaders) and external (billet families, parents) to the team environment.